Exploring planners' and public health practitioners' views on addressing obesity: lessons from local government in England. Issue 2 (6th April 2018) - Lake, Amelia A.; Henderson, Emily J.; Townshend, Tim G.
Abstract: Obesity is a complex health and social issue globally. The 2013 restructuring of Public Health in England resulted in a move from within the National Health Service to local government. The aim of this research was to understand the views of individuals working in public health and those working in spatial planning within local government on their respective responsibilities for addressing obesity through spatial planning. Spatial planning measures include planning policy, development control and built environment design at different scales. Findings identified a range of barriers for planners to be engaging with outcomes that can help reduce obesity. These include having an insufficient understanding of the causes of obesity and the importance of addressing obesity through multiagency approaches. They also include what was seen as a fragmentation in the health system and conflicting priorities. Our findings indicate that planners could be better engaged in the obesity agenda through formal incentives and also soft approaches. Formal approaches include written responsibilities within planners' job descriptions or regulations. Soft approaches include and aligning spatial and health priorities and providing planners with public health leadership roles.